2018
DOI: 10.1186/s12898-018-0164-1
|View full text |Cite
|
Sign up to set email alerts
|

Interference competition as a key determinant for spatial distribution of mangrove crabs

Abstract: BackgroundThe spatial distribution of mangrove crabs has been commonly associated with tree zonation and abiotic factors such as ground temperature and soil granulometry. Conversely, no studies were designed to investigate the role of competition for resources and predation in shaping crab distribution in mangroves, despite these biotic factors are recognised as key determinants for spatial patterns observed in the communities colonising rocky and sandy intertidal habitats.We studied floral and faunal assembla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 72 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…Such spatial heterogeneity occurs naturally in ecosystems and is maintained by spatio-temporal variations in a range of physical conditions in areas subjected to the impacts of benthic activity. Crab communities and their bioturbation intensity, for instance, vary as a function of tidal range, vegetation structure, microhabitat, and seasonality (Aschenbroich et al, 2016;Cannicci et al, 2018;Escapa et al, 2007;Li et al, 2018). The spatial scales of patchiness in the variables being measured are often not known before sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Such spatial heterogeneity occurs naturally in ecosystems and is maintained by spatio-temporal variations in a range of physical conditions in areas subjected to the impacts of benthic activity. Crab communities and their bioturbation intensity, for instance, vary as a function of tidal range, vegetation structure, microhabitat, and seasonality (Aschenbroich et al, 2016;Cannicci et al, 2018;Escapa et al, 2007;Li et al, 2018). The spatial scales of patchiness in the variables being measured are often not known before sampling.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Steinke et al (1993) observed that, if two crabs grab the same leaf when it falls, a fight will usually ensue with the stronger individual eventually pulling the leaf out of the other's grasp and retreating to its burrow. More recently, Cannicci et al (2018) proposed that interference competition for food may be a major force shaping the spatial distribution of sesarmids in the mangroves of Sri Lanka. Thus far, however, rigorous testing of hypothesis (i) or (ii) has not been undertaken.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…Goniopsis is a dominant species in Neotropical mangroves, and other crabs use burrows to protect themselves from their predatory habits (McNaughton and Wolf 1970, Ferreira et al 2013, Cannicci et al 2018). This crab is observed gnawing on the cortexes of red mangrove roots, which induces their sprouting (Calderon and Echeverri 1997).…”
Section: Interrelation Of Biotic and Abiotic Factors In Community Assemblagementioning
confidence: 99%